From negotiation to strategie: marital relationships and gender in São Paulo low - income women discourse - Souzas, Raquel; Alvarenga, Augusta Thereza de (Saúde e Sociedade, 2001)
This paper results from a wide monographic study on issues related to reproductive health of low-income women in the city of São Paulo, State of São Paulo, Brazil. It is based on the assumption that negotiation guidelines between couples can be disclosed through their discourse and that from these the marital relationships in terms of possibility or impossibility of negotiation, gender, conflicts and violence. Such issues are highly relevant for women's reproductive and sexual life. A qualitative field survey using the oral-thematic history technique was carried out with 16 women. The analysis is focused on the concepts of marriage and intimacy. The concept of power, sexuality and gender were articulated in the discussion. What meanings the concepts of marital relationships, infidelily. union and freedom acquire within the female discourse are also searched for in the analysis of the discourse. Detected in the discourse are the permanencies and changes that unveil the group's processes of "adaptation" and "modernization" within a context in which more up-to-date social and political relationships - characteristic of the new social era - are constructed.